MOSQUE AND ITS ROLE IN THE PROTECTION OF ORPHANS (Study at BKM Nurul Hidayah Jl. Garu II-A No. 26 Harjosari-I sub-district, Medan Amplas District) - Ismed Batubara, Yeltriana, Alkausar Saragih (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
The mosque is a ritual place of worship for the Islamic community which was ordered by Allah and His Messenger to prosper. In addition, the function of the mosque can also be maximized as a place to build social piety. Social piety is a good or pious deed that has a positive/beneficial impact on other people or society, for example helping the poor, giving scholarships for children from underprivileged families, for people who have abundant wealth, can do charity by wealth, alleviating poverty, building mosques, madrasas and others. For officials with power, he can make and oversee policies or rules that can improve the welfare of the people, help people who are left behind to get up and move forward. Piety descriptively is the embodiment of the concept of hablumminnas. so that they are classified as religious liars who are warned by Allah in Surah Al Maun (1-7). The purpose of this study was conducted to find out how the role of BKM Nurul Hidayah Jl.Garu II-A No.26 Harjosari-I Village, Medan Amplas District. The research method used is a qualitative research method with collection through observation, interviews, and documentation. Data analysis uses descriptive qualitative analysis techniques which are carried out by giving meaning to the data that has been collected, and then conclusions are drawn. That the function of the mosque has experienced a shift from a mere place of worship to a channel or channel of social piety in the form of protecting orphans in the form of sponsorship for orphans. Such a shift actually existed in the Age of Rasulullah SAW and BKM Nurul Hidayah Jl. Garu II-A No.26, Harjosari-I sub-district, Medan Amplas sub-district, has done this not to say, but to repeat what Rasulullah SAW has exemplified.